2014
DOI: 10.3109/08830185.2014.921162
|View full text |Cite
|
Sign up to set email alerts
|

Pathogen Infection as a Possible Cause for Autoimmune Hepatitis

Abstract: Autoimmune disorders afflicting the liver comprise the bona fide autoimmune diseases, primary biliary cirrhosis, primary sclerosing cholangitis, and autoimmune hepatitis as well as drug-induced autoimmune-like diseases, such as halothane hepatitis. Whereas drug-induced forms of acute or chronic hepatitis often have a clear triggering factor, the etiology of classical autoimmune liver diseases is only poorly understood. Besides a genetic component present in disease susceptible individuals, environmental trigge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 109 publications
0
20
0
Order By: Relevance
“…An additional strategy to induce AIH is based on the use of inflammatory viral vectors expressing Ags similar to, but not identical to, autoantigens, supporting the hypothesis of molecular mimicry of host structures by invading pathogens as a mechanism for the induction of autoimmune diseases (reviewed in Ref. 30). Using this strategy, it has been shown that self-antigens such as formiminotransferase cyclodeaminase or cytochrome P450 2D6 play an important role in the development of AIH (31).…”
Section: Discussionmentioning
confidence: 92%
“…An additional strategy to induce AIH is based on the use of inflammatory viral vectors expressing Ags similar to, but not identical to, autoantigens, supporting the hypothesis of molecular mimicry of host structures by invading pathogens as a mechanism for the induction of autoimmune diseases (reviewed in Ref. 30). Using this strategy, it has been shown that self-antigens such as formiminotransferase cyclodeaminase or cytochrome P450 2D6 play an important role in the development of AIH (31).…”
Section: Discussionmentioning
confidence: 92%
“…(45) Environmental exposures play greater roles than genetics in shaping the immune repertoire, and specific environmental factors, such as viral infections or xenobiotic exposures, can act as environmental triggers for loss of self-tolerance to autoantigens in persons genetically susceptible to AIH. (46,47) patHogeNeSIS Autoreactive CD4 and CD8 T cells break selftolerance to hepatic autoantigens as the result of environmental triggers and inability of autoantigen-specific natural T regulatory cells (nTregs) and inducible T regulatory cells (iTregs) to prevent autoreactivity (48)(49)(50) (Fig. 1).…”
Section: Genetic Predispositionsmentioning
confidence: 99%
“…Several case studies have revealed associations between pathogenic infections and the occurrence of AIH [2,3,7] . The presence of cross-reactive autoantibodies and the existence of structural similarities between AIH autoantigens and pathogens (i.e., molecular mimicry) provide a plausible explanation of how tolerance to liver autoantigens might be broken by infectious pathogens [8] . Experimental designs of AIH have clearly demonstrated that viral and bacterial superantigens can induce relapse and exacerbations of a T cell-mediated autoimmune process [9] .…”
Section: Discussionmentioning
confidence: 99%